Das Portfolio deutscher Biosphärenreservate im Lichte der Sustainable Development Goals - Hubert Job; Manuel Engelbauer; Barbara Engels (Raumforschung und Raumordnung, 2019)
This paper discusses the representativeness of the German Biosphere Reserves. The United Nations Sustainable Development Goals will serve as the theoretical framework of this analysis. Germany currently accounts a share of 16 % of the terrestrial land area under strict nature protection. This means that there is no quantity problem. Rather, the question arises about the number, geographical distribution and quality of protected areas – in this example Biosphere Reserves. So far, scientific papers only focus on the natural landscape representativeness of Biosphere Reserves in Germany. This is not enough for this category of protected areas as it rests on the paradigm of sustainable development. This is why this paper is focusing on possible structural and socioeconomic shortcomings in the network of German Biosphere Reserves. Therefore, precise indicators will be analysed in form of thematical maps to address selected Sustainable Development Goals. Furthermore, the existing Biosphere Reserves will be analysed if and to what extent they are able to reach their intended exemplary function towards "the rest of the world" as models for sustainable development.